DECOLONISING JOURNALISM EDUCATION IN SOUTH AFRICA critical perspectives. - Rodny-Gumede, Ylva.; Chasi, Colin; Jaffer, Zubeida; Ponono, Mvuso (ABINGDON : ROUTLEDGE, 2023)
This book is the culmination of several years of collaborative work. It is a unique contribution to the field of journalism because of the depth and variety of contributions it makes to the field. The scholars who contribute to this volume respond to the great need to rethink journalism from various perspectives including journalism training, research, the contents of the news media, language, media ethics, the safety of journalists and gender inequities in the news media. In doing this, they recognise how the societies that journalism address should themselves change.
Keywords: Journalism -- Study and teaching -- South Africa; Journalistic ethics -- South Africa; Educational equalization -- South Africa; Decolonization -- South Africa; LANGUAGE ARTS & DISCIPLINES / Journalism